Pandemi Covid-19 As A Factor of Delays in The Execution of Court Decisions - Dita Amalia; Dian Latifiani (Universitas Negeri Semarang, 2023)
Judicial decisions that have permanent legal force contain definite and permanent legal rights and positions between the litigating parties that must be realized through execution. Execution is a forced effort by the court against the defendants who don’t want to implement the judicial decisions voluntarily.The aim of this research is to know the factors that caused the delay in the implementation of the real execution in civil case No. 10/Pdt.G/2018/PN PWK Jo 93/Pdt/2019/PT BDG Jo 3532 K/Pdt/2019 at Purwakarta District Court. This research uses empirical legal research methods with a qualitative approach. To be able to obtain the necessary data, the authors use several methods, namely interviews and document analysis. The results of this research show that third-party resistance and the COVID-19 pandemic are factors causing the delay in the real execution of civil case no. 10/Pdt.G/2018/PN PWK Jo 93/Pdt/2019/PT BDG Jo 3532 K/Pdt/2019. In principle, even if there is resistance, the execution is not absolutely delayed unless the reason for the resistance is rational; in that case, the execution is delayed at least until the resistance is decided by the District Court. Meanwhile, health reasons and the government’s policy not to carry out activities that create crowds (Physical Distancing) are the basis for considering the COVID-19 pandemic as the cause of the delay in the real execution. Execution is the authority of the Head of the District Court in the form of policy. Thus, executions in civil cases have been delayed because of third-party resistance, and the COVID-19 pandemic is the policy of the Head of the District Court, which has been given by law. Execution is the authority of the Head of the District Court in the form of policy. Thus, executions in civil cases have been delayed because of third-party resistance, and the COVID-19 pandemic is the policy of the Head of the District Court, which has been given by law. Execution is the authority of the Head of the District Court in the form of policy. Thus, executions in civil cases have been delayed because of third-party resistance, and the COVID-19 pandemic is the policy of the Head of the District Court, which has been given by law.